EFFECT OF EXCHANGE RATES, INTEREST RATES, PROFITABILITY, AND SOLVENCY ON STOCK PRICES MEDIATED BY DIVIDEND POLICY - Salim, Ubud; Djumahir, Djumahir; Adilla, Nur' (Universitas Brawijaya, Indonesia, 2022)
The stock price of manufacturing companies listed on the Indonesia Stock Exchange fluctuates. It causes investors to experience difficulties in making investments in the stock market. A dividend policy is a policy in making decisions to distribute profits as dividends or withhold profits for business development. It is difficult for many company managers. This study examines and proves the effect of exchange rates, interest rates, profitability, and solvency on stock prices mediated by dividend policy. This study uses a quantitative approach with a sample of manufacturing companies listed on the Indonesia Stock Exchange. The number of observations was eight companies, with a research period of 4 years (2016-2019). Sampling using a purposive sampling method. Analysis of research data using multiple linear regression methods and path analysis. The results showed that solvency directly affects stock prices through dividend policy, while profitability only affects stock prices. The same test results also show that the exchange rate measured using exchange rate sensitivity and interest rates measured using interest rate sensitivity cannot influence the stock price of manufacturing companies. This study supports the signaling theory regarding the direct and indirect effects that lead to the company's stock price. Measuring financial ratios can help companies to decide on dividend policies. Company managers must manage the company's profitability and solvency appropriately to achieve the goals for shareholders'welfare.